The signaling power of the investment banks’ reputation on the performance of IPOs on Bursa Malaysia - Lin, Yong Tong; Rubi Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study examines the extent of the investment banks’ (IB) reputation, both high and low, affect the performance of the initial public offers (IPOs) on the Malaysian Main Board, Second Board and the MESDAQ market. Conventional and modified methodologies are used to measure the abnormal returns of the Malaysian samples between 2002 and 2008. The regression results based on the modified methods demonstrate that the reputation of IBs have significant influence over the performance of IPOs. However, the positive impact of the high reputation IBs (High IBs) is restricted to the Second Board over the short and medium terms but the negative influence of the low reputation IBs (Low IBs) is confined to the MESDAQ companies over the medium and the long terms. Contrary to many prior empirical studies, the reputation of the IBs does posses the signaling power to infer the future performance of IPOs.